Antidiabetic Effect of Tamarindus indica and Momordica charantia and Downregulation of TET-1 Gene Expression by Saroglitazar in Glucose Feed Adipocytes and Their Involvement in the Type 2 Diabetes-Associated Inflammation In Vitro. (4th July 2022) - Saxena, Madhukar; Prabhu, S. Venkatesa; Mohseen, M.; Pal, Amit Kumar; Alarifi, Saud; Gautam, Neelam; Palanivel, Hemalatha
Abstract : To date, there is no satisfactory and effective therapy available to cure type 2 diabetes mellitus (T2DM). This present work is focused on plant extracts and the effect of saroglitazar and TET genes on oxidative stress and inflammation in vitro adipocytes. Aqueous extracts of Tamarindus indica and Momordica charantia seed have shown potent antidiabetic activity that decreases glucose levels in diabetic adipocytes. After seven and fourteen days, the sugar level in the blood was significantly reduced when plant extracts were supplemented. Lipid profiles including total cholesterol (TC), triglyceride (TGL), high-density lipoprotein (HDL), low-density lipoprotein (LDL), and very low-density lipoprotein (VLDL) showed a highly significant change as expected in adipocytes treated with glucose compared with controlled adipocytes (P < 0.001 ). Gene expression of catalase, superoxide dismutase (SOD1, SOD2), and glutathione peroxidase (GPx) are changed twice, thrice, and quadruplet, respectively. The level of interleukin-1 (IL1) and tumor necrosis factor- α (TNF- α ) was restored but the interleukin-6 (IL6) and ten-eleven-translocation-1 (TET1) were completely knocked down by the use of saroglitazar. In comparison with the diabetic group, this supplementation significantly increased glycogen content and glucose-6-phosphate dehydrogenase activity. In the extract supplemented group, glucose-6-phosphatase, glucose-oxidizing enzyme, and glucose-phosphorylating enzyme activities were significantly reduced. After seven days of extract supplementation, these parameters were not resettled to a controlled level; however, after 14 days of supplementation, all parameters were restored to the control level. In addition to altering gene expression, TET enzymes may contribute to altered adiposity and its metabolic consequences. The purpose of this study is to examine new ideas and approaches for treating obesity, T2DM, and other associated metabolic disorders.